PEMANFAATAN TEKNOLOGI INFORMASI DAN PENERAPAN PENGENDALIAN INTERN KAS - Rahmaniar, Rahmaniar; Khairita. H (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
Internal cash control is a control process to achieve specific goals. Internal control is carried out by people from each organization, including management and all employees. Internal control is expected to provide reasonable assurance to managers and employees in an organization. The data analysis method in this study uses simple linear regression to predict the effect of independent variables. The population in this study amounted to 100 employees in the Aceh SKPD. The results showed that the use of information technology affected the implementation of internal cash control. However, it indicates that information technology can play an essential role in the performance of internal cash control in the Regional Work Unit (SKPD). By utilizing information technology, SKPD can improve efficiency and effectiveness in controlling and managing cash internally, such as identifying potential fraud or weaknesses in the cash control system, monitoring financial transactions in real-time, and making more accurate and transparent financial reports.